Pengaruh Kesadaran Merek dan Asosiasi Merek terhadap Ekuitas Merek pada Pelanggan Hypermarket di Kota Malang - Ermawati, Putri Wahyu; Sudiro, Achmad; Khusniyah, Nur (Jurnal Aplikasi Manajemen, 2016)
Abstract: This study aims to describe the direct influence brand awareness and brand associations to brand loyality and brand equity, and also theinfluence by brand awareness and brand associations of brand loyality whichis moderated to perceived quality.Direct influence of brand Ioyality brandequity, as well as explaining the influence of brand awareness and brand equ ty of the brand to the associations in mediation by brand loyality. The respo dents of this study amounts to 100 consumers in the Hypermarket Matahari Dept. Store in the Malang. Research Data collected by used questionnaire. S atistical analysis using method of analysis of the MRA and path analysis. The results showed that brand awareness and brand association had influence direct or indirect effects which has moderated by the perceived quality of brand loyalty. Brand Awareness and brand loyalty has a direct influence on brand equity, but does not indicate the existence of research results directly influence brand association of brand equity. The results also indicated that brand loyality affected the influence toward brand awareness and brand association against brand equity